Clinical features in patients of cough variant asthma with normal and high level of exhaled fractional nitric oxide. (2nd November 2016) - Tang, Wei; Zhou, Jun; Miao, Lili; Shi, GuoCao
Abstract: Objective: Cough variant asthma (CVA) is a subtype of asthma that is characterized by a chronic cough. The clinical characteristics and pulmonary function in patients with CVA who had normal and high exhaled fractional nitric oxide (FeNO) levels were compared. Methods: The clinical history and pulmonary function data from 99 patients with newly diagnosed CVA were collected. Result: Newly diagnosed subjects with CVA were divided into a high FeNO group (FeNO value over or equal to 25 ppb, n = 52) and a normal FeNO group (FeNO lower than 25 ppb, n = 47). There were more patients with coexistent allergic rhinitis or with family histories of allergic diseases in the high FeNO group. More patients in the high FeNO group reported that their chronic cough was triggered by allergen exposure. In the high FeNO group, the patients were younger than in the normal FeNO group. It was shown that baseline lung function tests were normal in all subjects, apart from a reduced midexpiratory flow rate (FEF25‐75). There was a significant decrease in FEF25‐75 in the high FeNO group compared with the normal FeNO group. No difference was found in the PD20 or the maximal FEV1 drop between the two groups. The multi‐factor logistic regression analysis showed that concomitant with allergic rhinitis was the high risk factor of a high FeNO in these subjects with CVA (OR = 5.03, 95% CI, 1.88‐13.49). Conclusion: CVA patients showed heterogeneity according to FeNO level. Patients with high FeNO level are more likely to experience symptoms associated with allergies.